Tricorythodes macuira (Ephemeroptera: Leptohyphidae), new species from Colombia - Martinez, Cristian E. Granados; Dias, Lucimar Gomes; Molineri, Carlos (Zootaxa, 2018)
Tricorythodes macuira sp n. is described and illustrated based on nymphs of both sexes and eggs from Colombia. This species can be recognized by the following combination of characters: maxillary palp 2-segmented and small, pronotum with rounded anterolateral projection, pronotum and mesonotum with thick and long setae on margins, femora I and II with transverse row of long setae at dorsum, tarsal claws with marginal row of 5–8 denticles and subdistal double row of 4-2 + 1-2 submarginal denticles, subtriangular operculate gills shaded black on a basal stripe, ventralmost lamellae of gills III–V with dorsal extension very well developed, abdominal segments VII–IX with small posterolateral spines. Eggs with one polar cap, polygonal chorionic plates with elevated margins and long adhesive filaments near the uncapped pole.